2018
DOI: 10.1177/2331216518805363
|View full text |Cite
|
Sign up to set email alerts
|

Objective Binaural Loudness Balancing Based on 40-Hz Auditory Steady-State Responses. Part II: Asymmetric and Bimodal Hearing

Abstract: In Part I, we investigated 40-Hz auditory steady-state response (ASSR) amplitudes for the use of objective loudness balancing across the ears for normal-hearing participants and found median across-ear ratios in ASSR amplitudes close to 1. In this part, we further investigated whether the ASSR can be used to estimate binaural loudness balance for listeners with asymmetric hearing, for whom binaural loudness balancing is of particular interest. We tested participants with asymmetric hearing and participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
6
1
Order By: Relevance
“…For instance, a CI is programmed through measuring the lowest current stimulation level that a patient can hear consistently (T levels) and the maximum comfortable level (C or MCL). MCLs are set with a minimal amount of current stimulation and gradually increased until the patient reports the sound is "loud but comfortable", thereby creating an electrical dynamic range (DR) for each CI electrode [3]. However, this programming method is not standardized, with techniques varying widely both between individual clinicians and between CI clinics [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a CI is programmed through measuring the lowest current stimulation level that a patient can hear consistently (T levels) and the maximum comfortable level (C or MCL). MCLs are set with a minimal amount of current stimulation and gradually increased until the patient reports the sound is "loud but comfortable", thereby creating an electrical dynamic range (DR) for each CI electrode [3]. However, this programming method is not standardized, with techniques varying widely both between individual clinicians and between CI clinics [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In their recent cohort study, Hoppe et al [ 13 ] showed that hearing performance in aided hearing-impaired listeners can typically be considered as asymmetrical. Against this background [ 33 , 34 ], a quantification of binaural hearing is needed for evaluation of the treatment. Numerous approaches have attempted to assess hearing performance in asymmetrical hearing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Various behavioral and evoked-response based measurements have been suggested to derive the interaural level mismatch in CI users ( Balkenhol et al, 2020 ). Most commonly “loudness balancing” is the reported fitting goal and as such also the mismatch measurement technique ( van Eeckhoutte et al, 2018 ; Veugen et al, 2016a ). However, just because this term is used does not mean that loudness balancing was actually performed (see section “causes of level mismatch”).…”
Section: Mismatch Measurement Techniques: Efficiency Limitations and ...mentioning
confidence: 99%
“…A very different approach is to use evoked, response-related measurements, allowing level estimates and balancing at specific stages of the auditory pathway, for example in the brainstem and midbrain by means of auditory brainstem response (ABR) amplitudes ( van Eeckhoutte et al, 2018 ) or late auditory evoked potentials (LAEP), which are more strongly correlated with loudness ( Hoppe et al, 2001 ). Similar to the loudness-scaling procedure, obtaining level-mismatch data via evoked-response-related measures is highly time consuming.…”
Section: Mismatch Measurement Techniques: Efficiency Limitations and ...mentioning
confidence: 99%